Іоноутворення метиленового блакитного на різних поверхнях - Gabovich, V. A.; Pokrovsky, V. A. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2011)
Mass-spectra have been studied of methylene dye on different substrates, namely, porous Ti, Au sputtered on mica, pyrolytic and thermally exfoliated graphite. The common features and differences in spectra were shown along with the peculiar properties of thermally exfoliated graphite.